PENGARUH UPAH MINIMUM PROVINSI (UMP), PENANAMAN MODAL ASING (PMA), DAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB), TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI IINDONESIA (STUDI KASUS 11 PROVINSI IPM LOWER MEDIUM) - Nailufar, Fanny; Juliansyah, Hijri; Murtala, Murtala; Risna, Risna (Jurnal Ekonomi Regional Unimal, 2024)
The purpose of this study was to analyse the effect of the Provincial Minimum Wage (UMP), Foreign Investment (PMA), and Gross Regional Domestic Product (PDRB) on the Human Development Index (IPM) in Indonesia (Case Study 11 Provinces IPM Lower Medium). This study uses secondary data for the period 2011 - 2021 obtained from the Central Statistics Agency (BPS). Data were analyzed using a panel data regression model. The results show that the variable  Provincial Minimum Wage (UMP) has a positive and significant effect on the Human Development Index (IPM) in Indonesia, Foreign Investment (PMA) has a negative and significant effect on the Human Development Index (IPM) in Indonesia, and Gross Regional Domestic Product (PDRB) has a positive and significant effect on the Human Development Index (IPM) in Indonesia.